2005
DOI: 10.1111/j.1365-2125.2004.02256.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of guidelines on the use of statins: analysis of prescribing trends 1998–2002

Abstract: Aims:To monitor statin prescribing trends over time in order to determine whether prescribers were influenced by study results and/or clinical guidelines in terms of type and dosage of statin prescribed. MethodsThe GMS (General Medical Services) prescription database in Ireland was used to identify a cohort of patients, prescribed statins, in order to investigate prescribing trends from January 1998-December 2002. Statin prescribing rates for patients with ischaemic heart disease and diabetes were compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
2
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 26 publications
3
41
2
3
Order By: Relevance
“…While a range of studies have explored the increasing statin utilization according to gender and age [2,4,[22][23][24][25], others have demonstrated that guideline implementation tend to increase in drug utilization [4,5,26]. However, it has been questioned whether statins are prescribed to those who benefit most i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While a range of studies have explored the increasing statin utilization according to gender and age [2,4,[22][23][24][25], others have demonstrated that guideline implementation tend to increase in drug utilization [4,5,26]. However, it has been questioned whether statins are prescribed to those who benefit most i.e.…”
Section: Introductionmentioning
confidence: 99%
“…During the last two decades, the utilization of statins (HMG-CoA reductase inhibitors) has increased considerably in most western countries [1][2][3][4][5], causing debates on the appropriateness of the prescribing pattern [6,7]. The beneficial effect of statins in patients with myocardial infarction (MI) and hypercholesterolemia was demonstrated in 1994, showing considerably reduced post-MI mortality in middle-aged men [8].…”
Section: Introductionmentioning
confidence: 99%
“…Il vero problema da risolvere è costituito dal fatto che le linee guida vengono seguite solo in parte dai medici e i pazienti trattati, anche se sono aumentati nel tempo, sono meno di quelli che dovrebbero essere; oltre a ciò, le terapie sono troppo discontinue e spesso si utilizzano dosi inadeguate [35][36][37].…”
Section: Effetti Pleiotropiciunclassified
“…Francesco Vittorio Costa (1) , Orietta Zaniolo (2) Farmeconomia e percorsi terapeutici 2007; 8 (1): [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] dal fungo Penicillum Citrinum, il primo inibitore dell'HMG-CoA reduttasi (compactina ML-236B). Infine, nel 1979, Hoffman e colleghi, nei laboratori della MS&D, isolarono da un ceppo del fungo Aspergillus Terreus, la prima statina d'impiego clinico: lovastatina.…”
unclassified
“…Following their increased utilization, controversies arose on their prescription patterns due to safety concerns [1][2][3][4][5][6][7]. Common adverse effects of statins include dyspepsia, flatulence, constipation, generalized gastrointestinal discomfort, elevated transaminase levels, myalgia, headache, sleep disorders and central nervous system disturbances [8].…”
Section: Introductionmentioning
confidence: 99%